METHODOLOGY FOR PSYCHOLOGY AS A SUBJECT OF SCIENTIFIC ANALYSIS - Семиченко, В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
In sttatius we consider the voices associated with the peculiarities of teaching psychology. The main features of the modern methodology of life are highlighted: formation of planetary thinking, ability to exist in conditions of global uncertainty of life, polysystemic way of existence, ability to decentralize, awareness of objective and subjective determinants of their activity. The psychological character of the main features of this methodology is stressed, which necessitates the increase in the society of attention to the mastery of each of its members by psychology as a way of streamlining individual and social life. The main tendencies of changes that occur in modern psychological education are generalized, it is argued that the effective realization of these tendencies is impossible without taking into account the peculiarities inherent in psychology as a branch of scientific knowledge and practical activity. The purpose of the article is as follows: analysis of the experience of teaching psychology, consideration of problems that arise from teachers and students in the process of mastering the subject, specification of tasks that are intended to perform a teaching methodology of psychology to enhance the psychological competence of those who study. Data on the periodicity of the publication of textbooks on the methodology of teaching psychology are presented. A clear tendency of growing attention to these problems is shown in the CIS countries as well as in Ukraine. The analysis of their content showed that the main focus of the authors is on questions that largely coincide with the textbooks on psychology. Insufficient attention is paid to the disclosure of the specifics of psychology at the methodological level. Three levels of functioning of teaching methods are considered, the problem of its classification as a certain branch of knowledge is emphasized. Demanding on the content of high psychological qualifications from the teacher, she official documents assigned to the branch of pedagogy. The tasks of teaching method are specified. The specifics of psychology as a subject of study are analyzed. On the basis of the conducted scientific analysis, the author's own experience of teaching, the inclusion of observation and the results of the survey of students and teachers, the difficulties are encountered in the process of studying and teaching psychological disciplines. Co-projected results of the process of studying psychology, as well as expectations of students from psychology teachers.